HUBUNGAN PENGETAHUAN TENTANG DAMPAK PENGGUNAAN HANDPHONE PADA KESEHATAN DENGAN PERILAKU PENGGUNAAN HANDPHONE PADA REMAJA - Tamsuri, Anas; Prakoso, Bayu (Akademi Keperawatan Pamenang, 2011)
Mobile phone is an electronic telecommunications device that has the same basic capabilities with conventional lines telephone and equipment, but it is compatible and easy to be taken anywhere and need not be connected with telephone network using a wired (wireless, wireless). Mobile phone transmitted electromagnetic waves to communicate with the nearest service station at the time used to send or receive short message or call or on the phone. In excessive amounts, this radiation of the electromagnetic waves harmful to the body health. The objective of this study was to determine the relationship of knowledge about the impact on health with the use of mobile phone usage behavior in adolescents. Design used in this study is cross sectional analytic. The population is all students of class XII of SMA 2 Pare, a number of 372 students. Sample of this study was number of 193 children by using simple random sampling technique. Collecting data for the independent variable : knowledge about the impact of mobile phone use on health and dependent variables, namely the behavior of mobile phone use in adolescents using questionnaires, was analyzed using cross tabulations and inferential, while to know the correlation relationships used Spearman correlations. Results from the study showed that respondents who have knowledge about the impact of mobile phone usage on health behavior is not necessarily good in using the mobile phone is also good. Research resulted that from 193 respondents, only 27 respondents (14.0%) who have good knowledge. And of those 27 respondents who have no good behavior, which behave quite 17 respondents (8.8%) and the remaining 10 respondents (of 10%) have less behavior. According to the result, it can be concluded that a sufficient knowledge may indicate favorable behavior.